Description de restes squelettiques de Latidae: Lates (?) sp. (Poissons téléostéens, Percoidei) du Miocène inférieur et moyen du bassin du Bas Tage (environs de Lisbonne, Portugal) - Antunes, M. Telles (2010)
Several Lower and Middle Miocene localities in the Lower Tagus basin near Lisbon yielded Latidae fragmentary remnants. No really decisive character has been recognized that would allow us to state these remnants could surely be ascribed to the genus Lates Cuv. & Val., although we regard this as nearly certain. There are some differences between the Miocene latidae under study and the type species Lates niloticus L. this suggests us to report the concerned remnants to a Lates (?) sp. that could belong to a new, hitherto undescribed species. The occurrence of Lates in fluviatile or lagoonal beds in the Lower Tagus basin Miocene series is not at all surprising under a paleoeciological view point. Even less if account is taken of the presence in the same levels of Siluriforms remnants belonging to Bagridae and Ariidae, two families that are well represented in Africa. Bagrid spines have been found at Quinta das Pedreiras in association with Lates (?) sp. remnants. The Lates (?) sp. discovery in the Lower and Middle Miocene from the Lower Tagus basin results in extending to the West this genus' biogeographic distribution. It is indeed the first discovery of this genus on Europe's Atlantic coasts. No matter which was the geographic origin of these fishes, they had to migrate several hundreds of kilometers through marine waters before entering the Tagus' estuary. The association of Lates (?) sp. remnants with Siluriform ones that have an extant, broad repartition in Africa south of the Sahara points out to an African origin. These thermophyll fishes imigration along the Atlantic coasts from lberian Peninsula probably has been possible owing to a warm climatic event that allowed them to migrate ca. 5 degrees (in latitude) northwards in Burdigalian times.